2021
DOI: 10.1039/d1ob01414e
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic dirhodium(ii,ii) paddlewheel complexes as carbene transfer catalysts

Abstract: This review highlights the applications of dirhodium(II,II) paddlewheel complexes with a mixed-ligand scaffold. Dirhodium(II,II) paddlewheel complexes are well-known as highly efficient and selective carbene transfer catalysts. While the majority of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 128 publications
0
9
0
Order By: Relevance
“…These bimetallic complexes have a "paddle wheel" (sometimes called "lantern") structure, containing a Rh-Rh single bond, the details of which has been subject to experimental and theoretical interrogations for decades. [1][2][3][4][5][6][7][8][9] These complexes-which have applications spanning from catalysis 10,11 and biology [12][13][14] to supramolecular chemistry [15][16][17][18] -are potent catalysts in organic chemistry because of their ability to promote nitrogen extrusion from diazo compounds to generate transient rhodium carbene intermediates (Scheme 1, center, L = CR2). These intermediates are capable of engaging in a wide range of chemical reactions including (2 + 1) cycloadditions (e.g., cyclopropanation, cyclopropenation, insertion into X-H bonds), various (n + 1) cycloaddition reactions where n > 2, and a diverse array of ylide reactions.…”
Section: Overview and Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…These bimetallic complexes have a "paddle wheel" (sometimes called "lantern") structure, containing a Rh-Rh single bond, the details of which has been subject to experimental and theoretical interrogations for decades. [1][2][3][4][5][6][7][8][9] These complexes-which have applications spanning from catalysis 10,11 and biology [12][13][14] to supramolecular chemistry [15][16][17][18] -are potent catalysts in organic chemistry because of their ability to promote nitrogen extrusion from diazo compounds to generate transient rhodium carbene intermediates (Scheme 1, center, L = CR2). These intermediates are capable of engaging in a wide range of chemical reactions including (2 + 1) cycloadditions (e.g., cyclopropanation, cyclopropenation, insertion into X-H bonds), various (n + 1) cycloaddition reactions where n > 2, and a diverse array of ylide reactions.…”
Section: Overview and Historical Contextmentioning
confidence: 99%
“…Dirhodium tetracarboxylate complexes (Scheme , left) are among the most commonly used catalysts in organometallic chemistry. These bimetallic complexes have a “paddle wheel” (sometimes called “lantern”) structure, containing a Rh–Rh single bond, the details of which have been subject to experimental and theoretical interrogations for decades. These complexeswhich have applications spanning from catalysis , and biology to supramolecular chemistry are potent catalysts in organic chemistry because of their ability to promote nitrogen extrusion from diazo compounds to generate transient rhodium carbene intermediates (Scheme , center, L = CR 2 ). These intermediates are capable of engaging in a wide range of chemical reactions including (2 + 1) cycloadditions (e.g., cyclopropanation, cyclopropenation, insertion into X–H bonds), various ( n + 1) cycloaddition reactions, where n > 2, and a diverse array of ylide reactions. The efficiency and selectivity imparted by dirhodium tetracarboxylate catalysts, including enantioselectivity when chiral carboxylate (or related) ligands are used, makes them especially useful tools in the construction of complex organic molecules. While one of the two rhodium atoms is involved directly in bond-making/breaking with substrates, the other is crucial for the overall catalytic performance of the complex, as it is involved in compensating for electronic alterations during a reaction (a phenomenon referred to as the trans effect or trans influence). , …”
Section: Introductionmentioning
confidence: 99%
“…[59,60] While this result implies that paddlewheel complexes with a mixed ligand sphere provide entirely new opportunities for asymmetric synthesis, a better understanding for how they operate and why they might be uniquely effective in certain cases remains yet to be gained. [61] As a first important step towards this end, it was decided to investigate the electronic structure of such paddlewheel complexes in depth.…”
Section: The Role Of Equatorial Ligandsmentioning
confidence: 99%
“…[59,60] Heteroleptic paddlewheel complexes in general are rare and their catalytic relevance has not yet been mapped in any systematic way. [61] In this specific case, indirect evidence suggested that the formation of the stannylated cyclopropanes takes place at the rhodium center ligated to the N-atom of the acetamidate of [Rh 2 ((R)-TPCP) 3 (acam)]; hydrogen bonding between the incoming diazoester and the protic À NH function seems to play a decisive role. [59,60] Be that as it may, the conclusion that the catalytic reaction likely occurs at the [O 3 ,N]-rather than the [O 4 ]-face of [Rh 2 ((R)-TPCP) 3 (acam)] was non-intuitive given the fact that carboxamidates usually entail lower reactivity than carboxylate ligands (see above).…”
Section: Introductionmentioning
confidence: 96%
“…The answer to this question could even be of more fundamental relevance beyond the present application. Although a number of heteroleptic dirhodium paddlewheel complexes are known in the literature, , truly convincing examples are rare in which they provided more than just gradual improvements of the results obtained with their homoleptic cousins. Complex C1 clearly marks such a case. The lessons to be learnt from it may therefore open new vistas for catalyst design and ultimately lead to strategic innovation in cyclopropanation chemistry in general. , …”
Section: Introductionmentioning
confidence: 99%